2007
DOI: 10.1371/journal.pmed.0040269
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of LPS-Induced Acute Lung Injury in Mice by Mesenchymal Stem Cells Overexpressing Angiopoietin 1

Abstract: BackgroundThe acute respiratory distress syndrome (ARDS), a clinical complication of severe acute lung injury (ALI) in humans, is a leading cause of morbidity and mortality in critically ill patients. ALI is characterized by disruption of the lung alveolar–capillary membrane barrier and resultant pulmonary edema associated with a proteinaceous alveolar exudate. Current specific treatment strategies for ALI/ARDS are lacking. We hypothesized that mesenchymal stem cells (MSCs), with or without transfection with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

30
480
3
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 559 publications
(520 citation statements)
references
References 77 publications
30
480
3
7
Order By: Relevance
“…Bone marrow stromal cells (BMSCs) have recently been shown to suppress harmful immune responses in patients with acute graftversus-host disease (4,5) and in several animal models of allogeneic rejection (6)(7)(8), a variety of autoimmune diseases (9)(10)(11), and lung injury (12)(13)(14)(15). The authors of many of these studies concluded that BMSC-driven immunosuppression results from a shift in Th1/Th2 balance (8,16,17).…”
mentioning
confidence: 99%
“…Bone marrow stromal cells (BMSCs) have recently been shown to suppress harmful immune responses in patients with acute graftversus-host disease (4,5) and in several animal models of allogeneic rejection (6)(7)(8), a variety of autoimmune diseases (9)(10)(11), and lung injury (12)(13)(14)(15). The authors of many of these studies concluded that BMSC-driven immunosuppression results from a shift in Th1/Th2 balance (8,16,17).…”
mentioning
confidence: 99%
“…Recently, allogeneic MSC have been studied in several in vivo models of lung disease (22)(23)(24)(25). Despite initial interest in their multipotent properties (26,27), engraftment in the lung does not appear to play a major role.…”
mentioning
confidence: 99%
“…Pathophysiologic mechanisms of ALI and ARDS include inflammation and increased endothelial and epithelial permeability to protein, resulting in extravascular accumulation of protein-rich edema fluid and alveolar epithelial injury (1). Several preclinical studies have demonstrated that bone marrow-derived mesenchymal stem (stromal) cells (MSCs) reduce the severity of ALI induced by endotoxin (2,3), live Escherichia coli bacteria (4,5), or following sepsis (6)(7)(8). Much of the therapeutic benefit of MSCs appears to derive from the release of paracrine soluble factors, which stabilize the injured alveolar epithelium and lung endothelium, reduce inflammation, increase the absorption of pulmonary edema fluid, and have antimicrobial activity (9).…”
mentioning
confidence: 99%